Stroke in Duchenne Muscular Dystrophy: A Retrospective Longitudinal Study in 54 Patients - Winterholler, Martin; Hollaender, Christian; Kerling, Frank; Weber, Irina; Dittrich, Sven; Türk, Matthias; Schröder, Rolf (Stroke, 2016)
Duchenne muscular dystrophy (DMD) is the most frequent skeletal muscle myopathy. Nearly all patients develop cardiomyopathy in their second decade of life. The purpose of this study was to evaluate the frequency, cause, and outcome of stroke in a German cohort of patients with DMD.Retrospective analysis of medical records of 54 DMD patients, who lived in a regional facility for handicapped people (Wichernhaus Altdorf, Germany) between 1963 and 2013.Fifty-four DMD patients were followed up for 7.4 years on average. Mean age at admission and discharge from the long-term care facility or death were 11.4 and 18.8 years, respectively. Covering a total observation period of 400 patient-years, we identified 4 DMD patients with juvenile arterial ischemic strokes. Off-label systemic thrombolysis in 2 patients resulted in a nearly complete regression of stroke-related symptoms, but 1 patient died of septic pneumonia and cardiac failure 24 days after thrombolysis therapy. In the other 2 patients, who had their ischemic strokes in 1994 and 1998, severe infarction-related symptoms persisted, and 1 patient died 13 days later. DMD-associated cardiomyopathy without evidence of atrial fibrillation was the only risk factor for ischemic stroke in all patients.This study indicates an increased risk for ischemic strokes in DMD patients. Regular cardiological assessment of all DMD patients is mandatory to evaluate the individual risk profile for cardioembolic events and to adapt therapeutic strategies.
EVALuna2:7328